Regulatory B Cells Dysregulated T Cell Function in an IL-35-Dependent Way in Patients With Chronic Hepatitis B - Liu, YaYun; Luo, Ying; Zhu, Tong; Jiang, Meng; Tian, ZhaoFeng; Tang, GuSheng; Liang, XueSong (Frontiers in Immunology, 2021)
Interleukin (IL)-35-secreting B (IL-35+B) cells are critical regulators in autoimmune and infectious diseases and exert suppressive functions in parallel with IL-10-producing B (B10) cells. However, the role of IL-35+B cells in persistent hepatitis B virus (HBV) infection remain unclear. To elucidate the role of IL-35+B cells in the progress of chronic HBV infection, we determined the frequency of IL-35+B cells and their relationship with the classical human regulatory B cell (Breg) subsets, namely, CD19+CD24hiCD38hi and CD19+CD24hiCD27+. Then, the regulatory effect and mechanism of Bregs on effector T cells were investigated in vitro. Here, we found that compared with healthy controls, the frequency of IL-35+B cells was increased in patients with chronic HBV infection and was enriched in human classical Breg subset CD19+CD24hiCD38hi B cells. Moderate correlation was observed between the frequency of IL-35+B cells and alanine aminotransferase levels (Spearman r = 0.401), but only mild correlation was noted between the frequency of IL-35+B cells and HBV DNA level (Spearman r = 0.314). The frequency of IL-35+B cells was negatively correlated with interferon-γ (IFN-γ)-producing CD4+ and CD8+ cells but positively correlated with IL-4-producing T cells. Bregs dysregulated T cell function through an IL-35-dependent mechanism and depended on cell-to-cell contact. In conclusion, IL-35+B cells were enriched during persistent HBV infection and dysregulated T cell balance in parallel with B10 cells.